2003
DOI: 10.1016/s0735-1097(03)00629-6
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of hypercholesterolemia-related impairment of angiogenesis by oral folate supplementation

Abstract: Ischemia-induced angiogenesis was inhibited by HC, which was rescued by oral folate supplementation, at least in part, via an NO-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…It is interesting to note that circulating cGMP levels before folate therapy were similar to those found in type 2 diabetic patients while, after folate therapy, cGMP was significantly increased to levels found in normal subjects (41). To our knowledge, these data with regard to the effects of folate on cGMP levels have never been reported in humans but are in accordance with previous results in rats, demonstrating that ischemia-induced angiogenesis was rescued by oral folate via an NO-dependent mechanism (42). In particular, the authors found increased tissue nitric oxide and, in turn, cGMP concentrations which correlated with increased serum folate levels, supporting our data of a folate-dependent increase in cGMP levels, a new mechanism of action of folate treatment.…”
Section: Discussionsupporting
confidence: 89%
“…It is interesting to note that circulating cGMP levels before folate therapy were similar to those found in type 2 diabetic patients while, after folate therapy, cGMP was significantly increased to levels found in normal subjects (41). To our knowledge, these data with regard to the effects of folate on cGMP levels have never been reported in humans but are in accordance with previous results in rats, demonstrating that ischemia-induced angiogenesis was rescued by oral folate via an NO-dependent mechanism (42). In particular, the authors found increased tissue nitric oxide and, in turn, cGMP concentrations which correlated with increased serum folate levels, supporting our data of a folate-dependent increase in cGMP levels, a new mechanism of action of folate treatment.…”
Section: Discussionsupporting
confidence: 89%
“…According to the results, we selected 14 days of injection because it caused significant A␤ production. Then, we injected the rats with two different dosages of Hcy (400 g/kg/day or 1600 g/kg/ day) with or without a simultaneous supplement of folate (4 mg/kg/day) and vit-B12 (250 g/kg/day) through drinking water 34 for 14 days. The injection was performed each day from 9:00 AM to 2:00 PM and the animals were sacrificed 24 hours after the final injection following measurement of spatial memory.…”
Section: Animals and Drug Administrationmentioning
confidence: 99%
“…27,28 In addition, ischemia-induced angiogenesis is reduced in eNOS knockout mice, 29 and in rat models, oral folate can rescue this process in a NO-dependent manner. 30 eNOS production of NO depends on the cofactor BH 4 . 31 The active form of folic acid, 5-methyltetrahydrofolate, restores BH 4 to allow participation in eNOS reactions.…”
Section: Psma Expression In Tumor Neovasculaturementioning
confidence: 99%